Circulatory Level of Inflammatory Cytoskeleton Signaling Regime Proteins in Cancer Invasion and Metastasis - Singh, Abhinay Kumar; Batra, Atul; Upadhaya, Ashish Datt; Gupta, Subhash; K P, Haresh; Dey, Sharmistha (Frontiers in Oncology, 2022)
Early detection of metastasis breast cancer (MBC) is the serious issue to healthcare system. It is essential to develop potential non-invasive, low-cost molecular biomarkers. The present study explored specific serum proteins of inflammatory, MAPK and cytoskeletal signaling pathways, involved in progression of MBC to establish panel of blood based diagnostic and prognostic biomarker. Healthy-control (HC), non-metastasis (NM) and metastasis (M) (pre and post-therapy) BC patients were recruited. LOX5, Rac1, Rac1b, p38α, phospho-p38α(Y182), LIMK1, phospho-LIMK1(T508), cofilin1 and phospho-cofilin1(S3) were quantified in the serum of study group by real time label free surface plasmon resonance technology and verified by western blot. Proteins were found to be significantly elevated in serum of BC patients compared to HC and also higher in M compared to NM which further downregulated in post-therapy M patients. Elevation of phospho-LIMK1 and phospho-cofilin1 which are critical for M were also indicated in the serum level and can differentiate from NM. ROC derived AUC(0.9) is very strong to differentiate between HC and BC. Moreover, the combined ROC of 3 molecules phospho-LIMK, p38α, phospho-p38α were found to be potent predictive panel of biomarker between M and NM with AUC0.95. The panel of inflammatory cytoskeleton signaling regime proteins specified in this study will have significant clinical utility for diagnosis as well as prognosis of MBC at early stage. The study may have a high translational value in simple and cost-effective way by avoiding frequent CT/PET scans.